Evolution of Romanian Imports and Exports in 2022, The Year with the Highest Inflation - Ioana Claudia Dobre (Ovidius University Annals: Economic Sciences Series, 2023)
The paper analyses the impact of the significant increase in inflation in 2022 on the volume of imports, exports and GDP in Romania. Using a quantitative analysis, the value of the indicators will be compared over the last 2 years, before and during the inflation of over 13%, using half-yearly data. The result of the analysis undertaken is that inflation has had an impact on imports, with the value of imports fluctuating significantly in 2022 compared to previous years and compared to exports and GDP.